Streets Of Royal Town: Exploring The Physical Character Of Traditional Street In The Malay Royal Town - Wan Norisma Wan Ismail; Nor Haslina Ja'afar; Nor Zalina Harun (Academic Research Publishing Group, 2024)
Special Issue 6